Extremely High Systemic Immune Inflammation Levels Increase the Risk of All-Cause and Cardiovascular Mortality in Postmenopausal Women - Wu F; Yang J; Liu Y; Zhang Y (International Journal of Women's Health)
Fei Wu,1 Jiantong Yang,1 Yinchuan Liu,1 Yipei Zhang2 1Department of Gynecology, Jiangxi Maternal and Child Health Hospital, Nanchang, Jiangxi, 330006, People’s Republic of China; 2Department of Gynecology, Nanchang Hongdu Hospital of Traditional Chinese Medicine, Nanchang, Jiangxi, 330008, People’s Republic of ChinaCorrespondence: Yipei Zhang, Department of Gynecology, Nanchang Hongdu Hospital of Traditional Chinese Medicine, Nanchang, Jiangxi, 330008, People’s Republic of China, Email 1113772944@qq.comBackground: The systemic immune inflammation (SII) index provides a comprehensive assessment of inflammatory and immune status in patients with different diseases. However, it remains unclear whether the SII can be considered a valuable prognostic risk factor of all-cause mortality for postmenopausal women.Methods: We analyzed data from 1882 postmenopausal women enrolled in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. The Systemic Immune-Inflammation Index (SII) was calculated using peripheral blood cell counts and categorized into quartiles. Multivariable Cox proportional hazards models and restricted cubic spline analyses were employed to assess the association between SII and mortality outcomes.Results: Over a median follow-up period of 8 years, 13.5% individuals died, with 4% deaths attributed to CVD. Patients with extremely high SII levels experienced significantly higher all-cause and CVD mortality. Compared to the low SII group (Q1), the hazard ratio (HR) and 95% confidence interval (CI) for all-cause mortality risk were 0.96 (0.87, 1.07), 0.97 (0.88, 1.08), and 1.28 (1.16, 1.41) for Q2, Q3, and Q4, respectively. Similarly, the HR (95% CI) for CVD mortality in Q2, Q3, and Q4 were 1.02 (0.83, 1.24), 1.11 (0.92, 1.34), and 1.32 (1.10, 1.58), respectively. Including SII in addition to traditional risk factors resulted in a slight enhancement in mortality prediction capability.Conclusion: Among postmenopausal women, extremely high SII levels were identified as an independent risk factor for all-cause and CVD mortality.Keywords: systemic immune inflammation, mortality, postmenopausal women, women health, cardiovascular disease